EFFECT OF COMBINED EXPOSURE OF WATER-BORNE AND DIETARY NICKEL ON THE GROWTH PERFORMANCE OF CIRRHINA MRIGALA - A. Shafiq; S. Abdullah; M. Javed; S. Hayat; M. Batool (Journal of Animal and Plant Sciences, 2012)
An experiment under CRD was arranged to study the growth performance of Cirrhina mrigala as affected by a combined exposure of water-borne and dietary nickel at constant water temperature, pH and total hardness of 30ºC, 7.0 and 200 mg L-1, respectively. Three age groups viz. 45-, 65- and 90-day were used to determine their response in terms of wet weight, fork and total length gains. Chemically extra pure chloride compound of nickel was used to prepare stock solutions of desired dilution. The wet weight gain by the fish, Cirrhina mrigala showed statistically significant variations between treated and control mediums. Fish with nickel treatment gained significantly lower weight, fork and total length than that of the control fish. Feed intake by the fish reared in untreated medium (control) was significantly maximum as compare to treated medium that showed significantly better feed conversion ratio in control than treated fish. The condition factor varied significantly during 12 weeks of the study period. The 90-day fish showed significantly better growth as compared to 65- and 45-day fish. Correlation coefficients among physico-chemical variables and increase in weight (grown under water-borne and dietary nickel) showed positively significant correlation with total ammonia but negatively significant correlation with magnesium contents.
Keywords: water-borne; dietary; nickel; chronic exposure; growth; fish